Analisis Aktivitas Inhibitor Lipase Pankreas Derivat Asam Klorogenat Pada Biji Kopi Hijau Sebagai Antiobesitas Secara In Silico - Faridah Faridah; Wahono Sumaryono; Partomuan Simanjuntak; Rizki Riyadi Triwibowo (Fakultas Farmasi Universitas Pancasila, 2021)
Obesity or overweight is defi ned as the accumulation of abnormal or excessive fat in adipose tissue whichcan damage health.Several plants have been used empirically as antiobesity.This study aims to obtain candidate antiobesity compounds that act as pancreatic lipase enzyme inhibitors, fi nd some amino acids that involved on the active site of the receptors and modelling the interactions of these active compounds at antiobesity receptors.The study start with internal validation of the receptors used (4DOQ), then carried out the docking process for the native ligand, comparison compound (Orlistat) and each test compound with the same receptor. The softwares used are PLANTS, YASARA, ChemSketch, and Pymol. The results of the 4DOQ receptor validation have an RMSD value of 1.7097 Ǻ. The results of the docking score for orlistat (-65.3258), and 4 active compounds namely chlorogenic acid (-69,3009), 5-O-caff eoylquinat acid (-70.6911), 4,5-O-dicaff eoilkuinic acid (-85 , 3375), 5-Op-coumaroilkuinic acid (-67,1886). Amino acids that play a role in the affi nity on the active side of the ligand bond with the pancreatic lipase receptor are THR21 (Threonine), ASN84 (Asparagine), GLY19 (Glycine), GLN156 (Glutamine), ALA85 (Alanine), ILE63 (Isoleucine), ARG62 (Arginine) . The conclusion of this study there are 4 chemical compounds in green coff ee beans that are active as antiobesity with the mechanism of action of the pancreatic lipase enzyme inhibitor, namely chlorogenic acid, 5-O-caff eoylquinic acid, 4,5-O-diphoeilquinic acid, 5-op-coumaroilquinic acid.